Reactive oxygen species formation and its effect on CD4+ T cell-mediated inflammation - Shu, Panyin; Liang, Hantian; Zhang, Jianan; Lin, Yubin; Chen, Wenjing; Zhang, Dunfang (Frontiers in Immunology, 2023)
Reactive oxygen species (ROS) are produced both enzymatically and non-enzymatically in vivo. Physiological concentrations of ROS act as signaling molecules that can participate in a variety of physiological and pathophysiological activities, and play an important role in basic metabolic functions. Diseases related to metabolic disorders may be affected by changes in the redox balance. This review details the common generation pathway of intracellular ROS and discusses the harm to physiological functions when ROS concentration is too high to reach an oxidative stress state. We also summarize the main features and energy metabolism of CD4+ T cell activation and differentiation and the effects of ROS produced during aerobic glycolysis on CD4+ T cells. As the current treatment for autoimmune diseases damages other immune responses and functional cells in the body, inhibition of the activation of autoreactive T cells and the differentiation of effector T cells (Teffs) by targeting aerobic glycolysis or ROS production without damaging systemic immune function is a promising treatment option. Therefore, exploring the relationship between T cell energy metabolism and ROS as well as the T cell differentiation process provides theoretical support for discovering effective treatments for T cell-mediated autoimmune diseases.